Synthetic azobenzene-containing metal–organic framework ion channels toward efficient light-gated ion transport at the subnanoscale. Issue 41 (13th October 2021) - Qian, Tianyue; Zhao, Chen; Wang, Ruoxin; Chen, Xiaofang; Hou, Jue; Wang, Huanting; Zhang, Huacheng
Abstract : A light-gated sub-1 nm ion channel is fabricated by growing azobenzene (AZO)-containing mixed-ligand UiO-66 metal–organic framework (MOF) in a nanochannel. Light-induced conformational change of AZO efficiently controls ion flux through MOF channels. Abstract : Artificial nanochannels with diverse responsive properties have been widely developed to replicate the smart gating functionalities of biological ion channels. However, in these traditional nanochannels, common responsive molecules are usually too small to efficiently block the large channels under the closed states, leading to weak gating performances. Herein, we report carboxylated azobenzene-coordinated metal–organic-framework (AZO-MOF) ion channels with impressive light-gating properties. The AZO-MOF ion channels were synthesized by the confined growth of AZO-MOFs, composed of light-responsive AZO-containing ligands, non-responsive ligands and metal clusters, into ion-track-etched polymer nanochannels. The AZO-MOF ion channels with an appropriate number of AZO ligands showed a well-maintained crystalline and three-dimensional porous structure, including nanoscale cavities and subnanoscale windows for LiCl conduction. Meanwhile, the AZO-containing ligands bend and stretch upon light irradiation to open and close the pathways, thus gating the ion flux through the AZO-MOF ion channels with high on–off ratios up to 40.2, which is ∼2.3–30 times those of AZO-encapsulated MOF ion channels and AZO-modified nanochannels. This work suggests ways to achieve subnanoscaled gating of ion transport by angstrom-porous MOFs coordinated by stimuli-responsive ligands.